2015
DOI: 10.2320/jinstmet.j2015046
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Superplasticity of Ultrafine-Grained Rod-Like AZ61 Alloy Using High-Pressure Sliding

Abstract: Fig. 1 Schematic illustration of High Pressure Sliding (HPS). (a) Cross sectional view and (b) 3 dimensional views.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The intense shear strain introduced in the samples results in ultra ne grains. One advantage of the HPS process is that it can be applied to samples with practical shapes such as sheets and rods; so far, it has been applied to sheets of pure Al (99.99%), Al-Mg alloy, AZ61 Mg alloy, and 7000 series Al alloy [18][19][20] , as well as rods of pure Al (99.99%), Al-Mg alloy, AZ61 Mg alloy, 2000 series Al alloy, and 7000 series Al alloy [21][22][23] . The ca-pacity of the HPS machine was recently increased to 500 tons 24,25) , which allows the samples to be scaled up 24,25) .…”
Section: Introductionmentioning
confidence: 99%
“…The intense shear strain introduced in the samples results in ultra ne grains. One advantage of the HPS process is that it can be applied to samples with practical shapes such as sheets and rods; so far, it has been applied to sheets of pure Al (99.99%), Al-Mg alloy, AZ61 Mg alloy, and 7000 series Al alloy [18][19][20] , as well as rods of pure Al (99.99%), Al-Mg alloy, AZ61 Mg alloy, 2000 series Al alloy, and 7000 series Al alloy [21][22][23] . The ca-pacity of the HPS machine was recently increased to 500 tons 24,25) , which allows the samples to be scaled up 24,25) .…”
Section: Introductionmentioning
confidence: 99%
“…(HPS: High-Pressure Sliding) 加工 55) と呼ばれ,粉末の固化 60) をはじめ,多くの金属材料 [56][57][58][59] に利用されている.この HPS プロセスは棒状試料 [61][62][63][64] やパイプ状試料 65) にも適用可能であ ることが示されている.さらに,試料の逐次送りと組み合わ V i e w せることで,SPD 処理面積が拡大できることも示されてい る 66,67) .このような開発は,SPD プロセスの実用化を目指し たもので,最近のレビュー論文 68) でも詳しく解説されてい る.本研究では,HPS プロセス装置はむしろ小型にして,シ ンクロトロン光施設における高圧高温下でのその場 X 線解析 に使用する. HPT や HPS プロセスによる特性向上は,プロセス中に発 生する高密度の格子欠陥に起因している [69][70][71] .このような格 [72][73][74] やマルチアンビル装置 75,76) を用いて行われ ることが多い.これらは主に静水圧条件下で使用されるが, DAC の場合,Bridgman のアイデアに沿って,一方のダイヤ モンドアンビルを他方に対して回転させることで意図的に塑 性変形を導入できる 13) .Blank らは DAC を用いてせん断ひず みを導入した最初であり 77,78) ,Levitas らは DAC でひずみ導 A d v a n c e…”
Section: は じ め にunclassified
“…The performance and applicability of such SPD processes are enhanced by modification: among them are continuous ECAP [10,11], ECAP with parallel channels (ECAP-PC) [12], ECAP for drawing [13] and ECAP for plate [14], continuous HPT [15,16], incremental feeding HPT [17] and bulk HPT [18]. Recently, the process of high-pressure sliding (HPS) was developed so that it is applicable for grain refinement of samples in forms of sheet [19][20][21][22][23][24] and rod [25][26][27][28]. It was also demonstrated that the sample dimensions can be scaled up by combining an incremental technique with the HPS processing, named incremental feeding HPS (IF-HPS) [29,30] for sheets and by introducing multi-pass technique, named multi-pass HPS (MP-HPS) [28] for rods.…”
Section: Introductionmentioning
confidence: 99%